Emotional maturity, dispositional coping, and coping effectiveness among adolescent athletes. (March 2015) - Nicholls, Adam R.; Levy, Andrew R.; Perry, John L.
Abstract: Objectives: Although some scholars have suggested that coping is constrained by emotional maturity, little is known about the relationship between these constructs. In this paper we assessed a model that included emotional maturity, dispositional coping, and coping effectiveness. We predicted that emotional maturity would have a direct effect on coping effectiveness in addition to an indirect effect via task-, distraction-, and disengagement-oriented coping. Design: Cross-sectional. Methods: Seven hundred and ninety athletes completed measures of emotional maturity, dispositional coping, and coping effectiveness. The data was analyzed using structural equation modeling, which revealed partial support for our model. Results: Several of the predicted paths were significant. In particular, there was a significant path between emotional maturity and task-oriented coping, but the paths between emotional maturity and distraction- and disengagement-oriented coping were not significant. Conclusion: Our findings indicate that how an athlete copes might be limited by his or her level of emotional maturity, which provides further evidence that coping is constrained by maturation among adolescent athletes. Highlights: There was a significant path between emotional maturity and task-oriented coping. The emotional maturity and distraction-oriented coping path was insignificant. The emotional maturity and disengagement-oriented coping path was insignificant. The path between emotional maturity and coping effectiveness was significant.